Kejadian Hipertensi Dengan Status Gizi Di Wilyah Kerja Puskesmas Pampang Makassar Sulawesi Selatan - Wahyuni, Ria; Rosida, Rosida; Rosdiana, Rosdiana; Dunggio, Abdul Rivai Saleh; Bayuningrum, Pratiwi; Mahyudin, Mahyudin (Barongko: Jurnal Ilmu Kesehatan, 2023)
Hypertension is the third leading cause of death in Indonesia for all ages (6.8%) after stroke (15.4%) and tuberculosis (7.5%). (Ministry of Health, 2016). The number of people with hypertension is estimated at 15 million Indonesians, but only 4% are controlled, meaning they suffer from hypertension. It is more stated that 50% of sufferers are not aware of themselves as hypertensive sufferers because they do not change and avoid risk factors. The purpose of this study was to determine the relationship between overweight, healthy weight and underweight (BMI) with the incidence of hypertension at the Pampang Makassar Health Center. The research design uses quantitative descriptive research with the Simple Random Sampling research method using the Solfin Formula. Based on the research results from the table, it shows that from the results of statistical tests (hypotheses) carried out by the Chi-sqere test, it was obtained that p value = 0.255 Ho was accepted and Ha was rejected because p value = 0.255 > 0.05 so it was proven that there was no relationship between Underweight (BMI) with the incidence of hypertension in the PKM Pampang Makassar Outpatient Room. The conclusion is that there is a relationship between Overwight (BMI) and the incidence of hypertension in the outpatient room of the Pampang Makassar Health Center as many as 19 people (63%). There is a relationship between healtyweight (BMI) and the incidence of hypertension in the Pampang Makassar Health Center Outpatient Room by 14 (46%). There is no relationship between Underweight (BMI) and the incidence of Hypertension in the Pampsng Makassar Health Center Outpatient Room by 12 (40%)